Suara Naratif sebagai Bahasa Sinematik: Dol dalam Pembentukan Pendidikan Karakter Berbasis Trilogi Ki Hajar Dewantara di Bengkulu - Adinda Innayah Putri Lianni; Uus Karwati; Reni Haerani (Journal of Practice Learning and Educational Development, 2026)
Traditional musical instruments possess philosophical, historical, and social values ​​that can reveal past civilizations and serve as a medium for cultural communication (Mufarizuddin, 2022; Agustinus, 2024). In Bengkulu, the Dol serves as a symbol of cultural identity and the primary instrument in the Tabot ritual. It also contains educational elements such as mathematics, physics, and character building. This study analyzes the implementation of Ki Hajar Dewantara's Educational Trilogy—Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani—in preserving Dol as a cultural heritage. The research method employed a descriptive qualitative approach with literature analysis and the integration of quotations and empirical findings from various studies on organology, ethnomathematics, and character education. The results indicate that Dol can serve as a medium for character formation for the younger generation through role models of preservation, creative empowerment in the production process, and mentoring in musical practice. Dol preservation also faces challenges such as a lack of promotional media and the threat of a breakdown in the transmission of playing techniques. This study confirms that local culture-based education has strategic potential for revitalizing traditional musical instruments while strengthening students' character.